New Treatment Options for Metastatic Thyroid Cancer - Kunadharaju, Rajesh (Fed Pract, 2015)
Newer multitargeted kinase inhibitors show prolonged overall and progression-free survival in patients with metastatic differentiated and medullary thyroid cancers.